Designing accountability measures for health professionals: results from a community-based micro-credential: case study on Indigenous cultural safety - Angela Mashford-Pringle; Sharon Tan; Sterling Stutz; Gabriel Tjong (BMC, 2023)
Abstract Background: There is a widespread commitment to implementing anti-Indigenous racism with health organizations in Canada by introducing cultural safety staff training. In partnership with a public health unit in Ontario, Canada, we developed an evaluation tool to assess the performance of staff who completed an online Indigenous cultural safety education course. Aims: To develop an accountability checklist that could be used for annual employee performance reviews to assess the use and level of knowledge received in professional cultural safety training. Intervention: We co-created a professional development accountability checklist. Five areas of interest were identified: terminology, knowledge, awareness, skills, and behaviours. The checklist comprises of 37 indicators linked to our community collaborators' intended goals as defined in our partnership agreement. Outcomes: The Indigenous Cultural Safety Evaluation Checklist (ICSEC) was shared with public health managers to use during regularly scheduled staff performance evaluations. The public health managers provided feedback on the design, checklist items, and useability of the ICSEC. The pilot of the checklist is in the preliminary stage and data is unavailable about effectiveness. Implications: Accountability tools are important to sustain the long-term effects of cultural safety education and prioritize the wellbeing of Indigenous communities. Our experience can provide guidance to health professionals in creating and measuring the efficacy of Indigenous cultural safety education to foster an anti-racist work culture as well as improved health outcomes among Indigenous communities.